2019
DOI: 10.3906/sag-1807-275
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of breast artery as detected by mammography: association with coronary and aortic calcification

Abstract: Background/aim: Coronary artery calcification (CAC) and aortic calcification (AC) are significant risk factors for coronary atherosclerosis. This study investigated how breast arterial calcification (BAC) detected from routine mammography correlates with coronary artery calcification and aortic calcification. Materials and methods: A total of 404 female patients above 40 years of age who, within a 6-month period, had undergone thoracic computed tomography and mammography for various reasons were screened retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…13 In addition to being correlated with CAC, BAC has been correlated with aortic calcification. 14 Furthermore, among 499 women aged 40 to 79 years, the presence of BAC was found to precede the development of CAC after 9 years, suggesting that BAC may serve as a marker for the development of coronary artery calcification. 15 Breast arterial calcification also has been correlated with increased serum markers of inflammation and vascular injury including high-sensitivity C-reactive protein, triglycerides, homocysteine, and increased low-density lipoprotein/high-density lipoprotein ratio.…”
Section: Resultsmentioning
confidence: 96%
“…13 In addition to being correlated with CAC, BAC has been correlated with aortic calcification. 14 Furthermore, among 499 women aged 40 to 79 years, the presence of BAC was found to precede the development of CAC after 9 years, suggesting that BAC may serve as a marker for the development of coronary artery calcification. 15 Breast arterial calcification also has been correlated with increased serum markers of inflammation and vascular injury including high-sensitivity C-reactive protein, triglycerides, homocysteine, and increased low-density lipoprotein/high-density lipoprotein ratio.…”
Section: Resultsmentioning
confidence: 96%
“…Mammography, reflecting the composition of a part of the human tissues, offers us the possibility to use this diagnostic platform to recognize another morphological finding of interest that is not usually recorded in mammographic reports, such as BAC. In addition, there are data which support a stronger association between BAC and cardiovascular mortality, compared to arterial calcification in other locations, such as aortic, splenic, internal and external iliac, detected by computed tomography [ 8 ]. Millions of women worldwide undergo a mammogram annually or biannually.…”
Section: Discussionmentioning
confidence: 99%
“…As some studies have shown, there is an association between the presence of BAC and renal disease [ 4 ], stroke [ 5 ], peripheral vascular disease, low bone mass, carotid artery narrowing and, mainly, coronary artery disease [ 6 , 7 , 8 , 9 , 10 ]. Several studies have shown a strong association between the presence of BAC and cardiovascular mortality [ 1 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…В работе A.I. Soylu et al [31] ВАС определялся с помощью маммографии с использованием шкалы классификации, определенной N. Loberant et al [32]: отсутствие сосудистых кальцинатов было классифицировано как 0 ст., незначительные точечные кальцинаты -как I ст., крупные зернистые кальцинаты по типу «трамвайных рельсов» или в виде кольца менее чем в трех сосудах -как II ст., крупные зернистые кальцинаты в трех сосудах и более -как III ст. (рис.…”
Section: сосудистые кальцинаты как потенциальный фактор риска сердечно-сосудистых заболеванийunclassified